The correlation between experienced workplace incivility with the psychological well-being of employees: Hubungan antara experienced workplace incivility dengan kesejahteraan psikologis pada karyawan - Yuniasanti, Reny; Sari, Julia (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
This study aims to determine the relationship between experienced workplace incivility and the psychological well-being of employees. The research hypothesis is that there is a negative relationship between experienced workplace incivility and psychological well-being. The subjects in this study were 40 employees who filled out the experienced workplace incivility scale and the psychological well-being scale. The data analysis method used is the Pearson product-moment correlation. Based on data analysis, in testing the hypothesis of the relationship between experienced workplace incivility, a correlation coefficient of rxy -.368 (p<.005) is obtained, which means a negative relationship exists between experienced workplace incivility in employees. The coefficient of determination (R2) is .136 or 13.6%, and other factors influence the remaining 86.4%.